Expression, purification and in vitro biological activity from human recombinant BMP-2 produced by a novel approach - Bessa, Paulo C. (2006)
Bone morphogenetic proteins have promoted great biomedical interest due to their ability in inducing new bone formation when used as powerful osteoinductive components of several late-stage bone grafting products. Recombinant human bone morphogenetic protein-2 (rhBMP-2) is obtained from mammalian cell expressing systems in low amounts or from bacteria inclusion bodies after timeconsuming refolding methods. Thus, there is a need to establish novel approaches for producing rhBMP-2 in high yields by simple and cheap procedures.